Utilization of Gadgets for Making Civics Online Teaching Materials for Middle and High School Teachers in Garut Regency - Ade Suherman; Tetep Tetep; Ana Maulana; Arik Darojat; Reni Nurfaujiah (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstact Learning is a process of interaction between students and educators and learning resources in a learning environment. After the pandemic, the change in teaching patterns from conventional learning to online learning became a demand for every educator around the world. Every educator needs mastery of technology, methods, and learning design to support online learning and educators must ensure that teaching and learning activities continue, even though students are at home. The solution is that educators are required to be able to operate gadgets to design learning media as innovations by utilizing online media. This service activity aims to provide knowledge as well as practice the use of applications in gadgets, namely Canva in online learning during the covid-19 pandemic at the Garut Regency PPKn MGMP to utilize gadgets for the manufacture of teaching materials and learning media. The solution is to organize a workshop. This activity was attended by several participants with a national scope consisting of lecturers, students, teachers and prospective teachers at all levels of education. This workshop is open to the public which is the focus of service, namely MGMP PPKn Garut Regency and all junior and senior high school teachers. The workshop was held in one day with material on introducing the use of applications in gadgets to improve the quality of teaching and learning and using gadgets as teaching materials or learning media to support learning during the COVID-19 pandemic. The results of this service activity are: 1) Participants are given theoretical and practical material about the Canva application, 2) Participants are involved in workshop activities as well as given training on how to use the Cana application and are guided by the presenters through zoom meeting interactions, 3) In the final session each participant submit the tasks given by the presenters at the workshop activities via email and video display of zoom meeting interactions, 4) The results of the google form distributed to the majority of participants understand and can practice using the Canva application for online learning and are able to operate their respective gadgets as learning media. Abstrak Pembelajaran merupakan proses interaksi peserta didik dengan pendidik dan sumber belajar pada suatu lingkungan belajar. Setelah terjadinya masa pandemi perubahan pola mengajar dari pembelajaran konvensional ke pembelajaran daring menjadi tuntutan untuk setiap pendidik diseluruh dunia. Setiap pendidik dibutuhkan penguasaan teknologi, metode, dan desain pembelajaran untuk menunjang pembelajaran daring dan pendidik harus memastikan kegiatan belajar mengajar tetap berjalan, meskipun peserta didik berada di rumah. Solusinya, pendidik dituntut untuk mampu mengoperasikan gadget untuk mendesain media pembelajaran sebagai inovasi dengan memanfatkan media daring (online). Kegiatan pengabdian ini bertujuan untuk memberikan pengetahuan sekaligus mempraktikan penggunaan aplikasi dalam gadget yaitu canva dalam pembelajaran Daring di masa pandemic covid-19 pada MGMP PPKn Kabupaten Garut guna memanfaatkan gadget untuk pembuatan bahan ajar dan media pembelajaran. Solusianya kami menyelenggarakan sebuah workshop, Kegiatan tersebut diikuti oleh beberapa peserta dengan ruang lingkup nasional yang terdiri dari dosen, mahasiswa, guru dan calon guru disemua jenjang Pendidikan. Workshop ini terbuka untuk umum yang menjadi fokus pengabdian yaitu MGMP PPKn Kabupaten Garut dan semua guru smp serta sma sederajat. Workshop tersebut dilaksankaan dalam satu hari dengan materi kegiatan pengenalan penggunaan aplikasi dalam gadget guna meningkatkan kualitas belajar mengajar dan memanfaatkan gadget sebagai bahan ajar atau media pembelajaran dalam menunjang pembelajaran pada masa pandemic covid-19. Adapun hasil dari kegiatan pengabdian ini yaitu: 1) Peserta diberikan materi teori dan praktik tentang aplikasi canva, 2) Peserta terlibat dalam kegiatan workshop sekaligus diberikan latihan cara penggunaan aplikasi cana dan dipandu oleh pemateri melalui interaksi zoom meeting, 3) Di sesi akhir setiap peserta menyetorkan tugas yang diberikan pemateri pada kegiatan workshop melalui email dan tampilan video interaksi zoom meeting, 4) Hasil google form yang disebar kepada peserta mayoritas memahami dan bisa mempraktikan penggunaan aplikasi canva untuk pembelajaran daring serta mampu mengoperasikan gadgetnya masing-masing sebagai media pembelajaran.